The Connection of Distribution of Envelope of Quasi-Harmonic Stochastic Process with Basic Two-Dimensional Distribution - V. A. Danilov; L. V. Danilova (Известия высших учебных заведений России: Радиоэлектроника, 2016)
The method of modeling of stationary stochastic process with given two-dimensional distribution is considered. The using of modeling of quasi-deterministic harmonic oscillation with given parameters underlies. By the instrumentality of modification the connection of characteristic function with given two-dimensional distribution is determined.